A structural and functional specification of a SCIM for service interaction management and personalisation in the IMS - Tsietsi, Mosiuoa Jeremia (Rhodes University, Faculty of Science, Department of Computer Science, 2012)
The Internet Protocol Multimedia Subsystem (IMS) is a component of the 3G mobile network that has been specified by standards development organisations such as the 3GPP (3rd Generation Partnership Project) and ETSI (European Telecommunication Standards Institute). IMS seeks to guarantee that the telecommunication network of the future provides subscribers with seamless access to services across disparate networks. In order to achieve this, it defines a service architecture that hosts application servers that provide subscribers with value added services. Typically, an application server bundles all the functionality it needs to execute the services it delivers, however this view is currently being challenged. It is now thought that services should be synthesised from simple building blocks called service capabilities. This decomposition would facilitate the re-use of service capabilities across multiple services and would support the creation of new services that could not have originally been conceived. The shift from monolithic services to those built from service capabilities poses a challenge to the current service model in IMS. To accommodate this, the 3GPP has defined an entity known as a service capability interaction manager (SCIM) that would be responsible for managing the interactions between service capabilities in order to realise complex services. Some of these interactions could potentially lead to undesirable results, which the SCIM must work to avoid. As an added requirement, it is believed that the network should allow policies to be applied to network services which the SCIM should be responsible for enforcing. At the time of writing, the functional and structural architecture of the SCIM has not yet been standardised. This thesis explores the current serv ice architecture of the IMS in detail. Proposals that address the structure and functions of the SCIM are carefully compared and contrasted. This investigation leads to the presentation of key aspects of the SCIM, and provides solutions that explain how it should interact with service capabilities, manage undesirable interactions and factor user and network operator policies into its execution model. A modified design of the IMS service layer that embeds the SCIM is subsequently presented and described. The design uses existing IMS protocols and requires no change in the behaviour of the standard IMS entities. In order to develop a testbed for experimental verification of the design, the identification of suitable software platforms was required. This thesis presents some of the most popular platforms currently used by developers such as the Open IMS Core and OpenSER, as well as an open source, Java-based, multimedia communication platform called Mobicents. As a precursor to the development of the SCIM, a converged multimedia service is presented that describes how a video streaming application that is leveraged by a web portal was implemented for an IMS testbed using Mobicents components. The Mobicents SIP Servlets container was subsequently used to model an initial prototype of the SCIM, using a mUlti-component telephony service to illustrate the proposed service execution model. The design focuses on SIP-based services only, but should also work for other types of IMS application servers as well.
Keywords: Internet Protocol multimedia subsystem; Internet Protocol multimedia subsystem -- Specifications; Long-Term Evolution (Telecommunications); European Telecommunications Standards Institute; Wireless communication systems; Multimedia communications